MODERN PROBLEMS OF LANGUAGE LEARNING AND TEACHING (KOREAN LANGUAGE) (CAHIERS MAGELLANES-NS, 2024)
This study raises questions about linguistic phenomena and their learning. A separate complex question is raised about the connection between thought and speech, the relationship between lexical and grammatical semantics, and methods of teaching both language and literature. This article presents issues of speech activity and communication. In studies of speech activity, it has been established that almost every speech utterance contains speech phenomena that are not provided either by the language system, or by the norm of language, or by use. This article also discusses motivational sentences in Korean. This fact forces syntactic science to solve current problems of communication and cognition. The issue of teaching language and literature is also a pressing issue in linguistics. This is due to the fact that knowledge of a language is one goal, another goal is to transfer this knowledge. Teaching language and literature to different students is a particularly complex issue across the entire methodological structure. Some questions and decisions taken can, to some extent, be used in the process of educational and pedagogical activities. Key words: Methodology, educational technologies, semantics, linguistics, Korean language, oral speech, structure, vocabulary, research, proposal